Preparation and research of brush-coated solvent-free polyurethane anti-corrosion coatings. Issue 1 (February 2020) - Han, Zhongzhi; Shi, Jiafeng; Ding, Chao; Li, Shi; Cui, Cancan; Duan, Shaoming; Wang, Lei; Guo, Xiaojun
Abstract: In order to solve the problem of short gel time and difficulty in brushing of solvent-free polyurethane coatings, the coatings choose polyether polyester polyol and polyisocyanate prepolymer as the main film-forming materials, adding spherical ceramic powder to improve the wear resistance of the coating, combination of molecular sieve physical dehydration and oxazolidine chemical dehydration, effectively solves the problem of water sensitivity of paint, a solvent-free polyurethane anticorrosive coating for brush application was prepared. The coating also has good adhesion, excellent wear resistance and corrosion resistance.